IMPLEMENTATION OF THE ISLAMIC BANKING CONCEPT ON CUSTOMERS AS PARTNERS OF ISLAMIC BANKS IN THE PERSPECTIVE OF ISLAMIC DA'WAH - Asmawi, Moh; Rasyid, Daud; Wilestari, Median (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This research investigates the implementation of Islamic banking as a means to support da’wah, emphasizing the role of Islamic banks not only as financial institutions but also as platforms for disseminating Islamic values and promoting societal welfare. The study employs a mixed-method approach, integrating both quantitative and qualitative methods to provide a comprehensive and nuanced understanding of the phenomenon. Findings reveal that public awareness of the principles of Islamic banking remains relatively low. However, most customers of Islamic rural banks (BPR) in the Jabodetabek area perceive that Islamic banks have successfully implemented Islamic banking principles. This study further demonstrates that the social and economic impact of Islamic banking aligns strongly with the goals of Islamic da’wah by offering halal financial transaction alternatives and enhancing the connection between Islamic banking and Islamic da’wah. Key implications include the need for intensified education and socialization efforts, involvement of all stakeholders as educational agents, reinforcement of the Sharia Supervisory Board’s (DPS) role, improved transparency and justice, expanded outreach, and strengthened alignment between Islamic banking practices and da’wah objectives. This research contributes to understanding Islamic banking as an instrument for economic-based da’wah, highlighting its potential to influence financial behavior in alignment with Islamic principles.